EXHIBITION/EXPOSITION: Irigaray and Lacoue-Labarthe on the Theaters of Mimesis - Hadikoesoemo, Niki (Homo Mimeticus II, 2024)
This chapter is an investigation into the relationship between theater and mimesis based on the work of two contemporary French thinkers who have rarely been discussed together but who are at the forefront of the re-turn to mimesis - namely, Luce Irigaray and Philippe Lacoue-Labarthe. Following the mimetic turn in its "shift from a still dominant translation of mimesis as a representation of reality [to a] performative, embodied, affective, relational, and deeply troubling manifestation of mimesis" (Lawtoo 2022, 31-33), my aim in this chapter is to put the notion of theater at the forefront of materialized processes of imitation.